Transcatheter Aortic Valve Implantation in Nonagenarians. Issue 6 (November 2016) - Penkalla, Adam; Kempfert, Joerg; Unbehaun, Axel; Buz, Semih; Drews, Thorsten; Pasic, Miralem; Falk, Volkmar
Abstract : Objective: In this report, we assess the outcome of transcatheter aortic valve implantation (TAVI) in nonagenarians at our institution during a 6-year period. Methods: Between April 2008 and July 2014, 40 patients with a mean ± SD age of 91.8 ± 2.3 years (range, 90–98 years) underwent TAVI. Thirty-three patients (82.5%) received transapical TAVI, and seven patients (17.5%) received transfemoral TAVI. Baseline characteristics were as follows: mean ± SD EuroSCORE II, 23.9 ± 14.21; mean ± SD Society of Thoracic Surgeons mortality score, 24.2 ± 11.4; mean ± SD SYNTAX score, 7.6 ± 9.3; mean ± SD NYHA class, 3.5 ± 0.5; mean ± SD transvalvular gradient, 46.8 ± 17.8 mm Hg; mean ± SD aortic valve area, 0.7 ± 0.2 cm 2 . Results: Intraoperative mortality was 2.5% and 30-day all-cause mortality was 10%. The actuarial survival rates at 1 and 5 years were 58.6% and 30.4%, respectively. Seven patients (17.5%) underwent simultaneous elective TAVI and percutaneous coronary intervention. Three patients (7.5%) were operated on with the use of cardiopulmonary bypass. No conversion to open surgery occurred. In transesophageal echocardiography assessment, no moderate or severe prosthetic aortic valve regurgitation was observed. Four patients (10%) had postoperative acute renal failure stage 3 and needed new dialysis ( P = 0.125). Three patients (7.5%) had a disabling stroke. Periprocedural myocardial infarction occurred in one patient (2.5%). Seven patients (17.5%) needed postoperative pacemaker implantation. Male sex and renal insufficiency were found to be predictors of mortality in univariable analysis. Conclusions: Transcatheter aortic valve implantation can be performed in nonagenarians despite very high preoperative risk scores and substantial multimorbidity, with acceptable outcomes.